(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In this article, the economic analysis of tax risks of foreign economic activity, the role of taxes in attracting foreign investors to our country, suggestions and recommendations are formed through foreign experiences that should be introduced.